Social Return on Investment (SROI) framework for measuring the real value of Sungai Muda flood mitigation program - Don Ramli Dona Raihana, Aiyub Kadaruddin, Arifin Kadir (Universiti Pendidikan Sultan Idris, 2016)
Social Return on Investment (SROI) framework for measuring the real value of Sungai Muda flood mitigation program by Don Ramli Dona Raihana, Aiyub Kadaruddin, Arifin Kadir,